Beta-cyclodextrin cross-linked porous oil-absorbing microspheres and preparation method thereof

CN122978356APending Publication Date: 2026-10-27XUZHOU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611481481.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]本申请的目的之一在于提供一种β-环糊精交联多孔吸油微球及其制备方法,以解决现有技术中吸油材料刚柔失衡导致吸附容量与机械稳定性矛盾以及孔道连通性差导致吸附动力学缓慢的问题

Benefits of technology

(1)本申请通过构建包含柔性烷基链段、刚性芳香链段及改性环糊精交联结构的三维网络,实现了刚柔协同平衡。柔性链段赋予网络高溶胀度以容纳大量油分子,刚性链段提供骨架支撑防止溶胀塌陷,改性环糊精既作为交联点维持网络完整性,又通过主客体包合作用增强吸附选择性与亲和力,从而兼具高吸油容量与高保油率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978356A_ABST
    Figure CN122978356A_ABST
Patent Text Reader

Abstract

The application relates to a beta-cyclodextrin crosslinked porous oil-absorbing microsphere and a preparation method thereof, and belongs to the technical field of high polymer adsorbing materials, at least solves the problems that the rigidity and flexibility imbalance of the oil-absorbing material in the prior art leads to the contradiction between the adsorbing capacity and the mechanical stability, and the poor pore connectivity leads to slow adsorbing kinetics. The application provides a beta-cyclodextrin crosslinked porous oil-absorbing microsphere, the beta-cyclodextrin crosslinked porous oil-absorbing microsphere has a three-dimensional crosslinked network, the three-dimensional crosslinked network comprises a flexible alkyl chain segment, a rigid aromatic chain segment and a modified cyclodextrin crosslinked structure; the beta-cyclodextrin crosslinked porous oil-absorbing microsphere has a multistage through-hole structure inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer adsorption materials technology, and in particular to a β-cyclodextrin crosslinked porous oil-absorbing microsphere and its preparation method. Background Technology

[0002] Currently, physical adsorption is widely used in the treatment of organic pollutants in water bodies and oil spills due to its simplicity and high efficiency. Among them, β-cyclodextrin-based polymeric oil-absorbing materials have attracted much attention due to their unique hydrophobic cavity structure. However, existing β-cyclodextrin-based oil-absorbing materials still face technical bottlenecks in practical applications: on the one hand, the balance between flexible alkyl segments and rigid aromatic segments in the polymer network is difficult to control. Excessive flexibility leads to network collapse and decreased oil retention after oil absorption, while excessive rigidity limits swelling and reduces adsorption capacity. On the other hand, the pore structure of the material is not well controlled. High specific surface area often cannot be converted into effective adsorption sites due to poor pore connectivity, resulting in slow adsorption kinetics. Therefore, there is an urgent need to develop an oil-absorbing material that combines high oil absorption capacity, excellent mechanical stability, and rapid adsorption kinetics. Summary of the Invention

[0003] One of the objectives of this application is to provide a β-cyclodextrin crosslinked porous oil-absorbing microsphere and its preparation method, so as to solve the problems in the prior art where the imbalance between rigidity and flexibility of oil-absorbing materials leads to a contradiction between adsorption capacity and mechanical stability, and the poor pore connectivity leads to slow adsorption kinetics.

[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: According to a first aspect of this application, this application provides a β-cyclodextrin crosslinked porous oil-absorbing microsphere, wherein the β-cyclodextrin crosslinked porous oil-absorbing microsphere has a three-dimensional crosslinked network, wherein the three-dimensional crosslinked network comprises flexible alkyl segments, rigid aromatic segments, and modified cyclodextrin crosslinked structures; the β-cyclodextrin crosslinked porous oil-absorbing microsphere has a multi-level through-pore structure inside.

[0005] Based on the above technical means, a three-dimensional network containing flexible alkyl segments, rigid aromatic segments, and modified cyclodextrin crosslinking structures is constructed to achieve a synergistic effect of rigidity and flexibility: the flexible segments provide the network with swelling space to accommodate oil molecules, the rigid segments provide skeletal support to prevent swelling collapse, and the modified cyclodextrin serves both as crosslinking points to maintain network integrity and as hydrophobic inclusion sites to enhance adsorption selectivity; at the same time, the internal multi-level through-pore structure provides rapid diffusion channels for oil molecules, significantly improving the adsorption kinetics performance.

[0006] In some optional embodiments, the flexible alkyl segment is copolymerized from long-chain alkyl ester monomers of acrylic acid or methacrylate and short-chain alkyl ester monomers of acrylic acid or methacrylate, the rigid aromatic segment is copolymerized from tert-butylstyrene monomers, and the modified cyclodextrin crosslinking structure is provided by an alkenyl-modified cyclodextrin crosslinking agent.

[0007] Based on the above technical means, by introducing the synergistic effect of long-chain and short-chain alkyl esters, long-chain alkyl esters provide the main hydrophobic swelling capacity and van der Waals adsorption sites, while short-chain alkyl esters help regulate the chain segment mobility and glass transition temperature, avoiding the crystallization tendency caused by pure long chains or the insufficient swelling caused by pure short chains; the benzene ring in the tert-butylstyrene monomer provides rigid support, and the tert-butyl group further enhances hydrophobicity and generates steric hindrance, hindering the penetration of polar molecules; the alkenyl-modified cyclodextrin crosslinking agent covalently integrates the cyclodextrin units into the network, avoiding the loss problem caused by physical blending and ensuring the long-term stability of the adsorption sites.

[0008] In some optional embodiments, the long-chain alkyl ester monomer of acrylic acid or methacrylate is dodecyl acrylate, the short-chain alkyl ester monomer of acrylic acid or methacrylate is butyl acrylate, and the tert-butylstyrene monomer is 4-tert-butylstyrene; the molar percentage of dodecyl acrylate is 40% to 60% based on the total mass of the polymeric monomers excluding the crosslinking agent, and the remaining polymeric monomers are composed of butyl acrylate and 4-tert-butylstyrene, wherein the molar percentage of 4-tert-butylstyrene is 5% to 55% of the total mass of butyl acrylate and 4-tert-butylstyrene; the alkenyl-modified cyclodextrin crosslinking agent is acryloyl-modified β-cyclodextrin, and its amount is 5% to 15% based on the total mass of the polymeric monomers excluding the crosslinking agent.

[0009] Based on the aforementioned technical methods, specific monomer types and ratio ranges were defined. The combination of dodecyl acrylate and butyl acrylate optimized the balance between chain segment flexibility and hydrophobicity; within the aforementioned molar ratio range, 4-tert-butylstyrene effectively enhanced network rigidity to maintain microsphere morphology without excessively restricting swelling due to high content; acryloyl-modified β-cyclodextrin, at a mass fraction of 5%–15%, provided sufficient hydrophobic cavities for host-guest inclusion adsorption while ensuring sufficient crosslinking density, thereby achieving the optimal match between adsorption capacity and structural stability.

[0010] In some optional embodiments, the multi-level through-pore structure comprises mesopores and micropores with an average pore size of 3.0–6.0 nm; the multi-level through-pore structure is formed by the phase separation and removal of a non-polar liquid alkane porogen during polymerization.

[0011] Based on the aforementioned technical methods, the compatibility difference between nonpolar liquid alkane porogens and polymer networks is utilized to induce phase separation during suspension polymerization. After removal, a multi-level interconnected structure containing mesopores and micropores is formed in situ. This pore size range (3.0–6.0 nm) matches the kinetic diameter of common oil and organic solvent molecules, which is beneficial for rapid capillary filling of oil molecules and enhances oil retention capacity through interfacial interactions between pore walls and oil molecules. This solves the contradiction of low oil retention rate of traditional macroporous materials or slow adsorption rate of microporous materials.

[0012] In some optional embodiments, the nonpolar liquid alkane porogen is n-dodecane; the BET specific surface area of ​​the hierarchical through-pore structure is 3.726–6.0 m². 2 / g, total pore volume is 0.002~0.010cm³ 3 / g, with an average pore size of 3.0–4.5 nm.

[0013] Based on the aforementioned techniques, n-dodecane was selected as the pore-forming agent. Its solubility parameters differ moderately from those of the reactants, enabling the formation of a uniform and well-connected phase-separated structure. Under these process conditions, specific pore structure parameters (BET specific surface area 5.0–6.0 m²) were obtained. 2 With an average pore size of 4.0–4.5 nm (g / g), it has been experimentally verified that this is the optimal window for achieving high oil absorption rate and rapid adsorption kinetics, ensuring the high efficiency of the material in practical applications.

[0014] In some optional embodiments, the β-cyclodextrin cross-linked porous oil-absorbing microspheres have a saturated oil absorption rate of ≥120 g / g for carbon tetrachloride and a saturated oil absorption rate of ≥90 g / g for xylene; the β-cyclodextrin cross-linked porous oil-absorbing microspheres have an oil retention rate of ≥90% for both carbon tetrachloride and xylene.

[0015] Based on the aforementioned technical methods, the core performance of the product was defined through quantitative indicators. The high saturation oil absorption ratio demonstrates the efficient storage capacity of oil molecules by the rigid-flexible synergistic network and the hierarchical porous structure; the high oil retention rate reflects the strong physical binding effect of the three-dimensional cross-linked network on oil molecules and the synergistic effect of the strong van der Waals forces between the hydrophobic segments and oil molecules, ensuring that no secondary leakage occurs during the collection and transfer process.

[0016] In some optional embodiments, the weight loss of the β-cyclodextrin crosslinked porous oil-absorbing microspheres after soaking in 18% HCl solution and 48% NaOH solution at 50°C for 48 h is <6%.

[0017] Based on the aforementioned technical methods, the material's excellent acid and alkali chemical stability was characterized. This is attributed to the conjugated stability of the benzene ring in the rigid aromatic chain segment and the strong hydrophobic shielding effect of the tert-butyl group, which effectively prevents the penetration of acid and alkali media into the polymer network and the hydrolytic attack on the ester groups, enabling the material to adapt to complex and harsh industrial wastewater or emergency treatment environments.

[0018] According to a second aspect of this application, this application provides a method for preparing β-cyclodextrin crosslinked porous oil-absorbing microspheres, used to prepare the aforementioned β-cyclodextrin crosslinked porous oil-absorbing microspheres. The method includes the following steps: preparing an aqueous dispersion containing a dispersant; adding an oil phase mixture containing a flexible alkyl monomer, a rigid aromatic monomer, a modified cyclodextrin crosslinking agent, an initiator, and a non-polar porogen to the aqueous dispersion, and carrying out a suspension polymerization reaction to obtain polymer microspheres; and solvent extracting the polymer microspheres to remove the non-polar porogen to obtain the β-cyclodextrin crosslinked porous oil-absorbing microspheres.

[0019] Based on the aforementioned techniques, a three-dimensional cross-linked network with a multi-level interconnected pore structure was constructed in one step using suspension polymerization combined with the phase separation pore-forming mechanism of a non-polar porogen. This method is simple, operates under mild conditions, and completely removes the porogen through solvent extraction, avoiding interference from residues on adsorption performance, making it suitable for industrial-scale production.

[0020] In some optional embodiments, the dispersant is polyvinyl alcohol, the initiator is benzoyl peroxide; the suspension polymerization reaction is carried out at a temperature of 70–90°C for a reaction time of 10–15 h; and the solvent extraction is performed by alternating washing with acetone and deionized water.

[0021] Based on the above technical methods, the polymerization process parameters were optimized. Polyvinyl alcohol, as a dispersant, provides a stable droplet dispersion system, ensuring uniform microsphere size; benzoyl peroxide has a moderate decomposition rate at 70–90℃, which is conducive to the formation of a regular cross-linked network; alternating washing with acetone and deionized water utilizes the principle of "like dissolves like" and polarity differences to efficiently remove residual porogens, unreacted monomers, and dispersants from inside the microspheres, ensuring product purity and pore unobstructed flow.

[0022] In some optional embodiments, the preparation method further includes a step of regenerating the β-cyclodextrin cross-linked porous oil-absorbing microspheres after oil adsorption: the β-cyclodextrin cross-linked porous oil-absorbing microspheres after oil adsorption are immersed in ethanol for washing, and then dried for recycling; after 10 cycles, the oil absorption ratio is maintained at ≥75%.

[0023] Based on the aforementioned technical methods, a material regeneration and recycling process was established. Ethanol, as a good solvent, can effectively displace oil molecules from the microsphere network and cyclodextrin cavities without damaging the polymer backbone structure. A cycle retention rate exceeding 75% demonstrates the material's excellent structural memory and fatigue resistance, significantly reducing long-term operating costs and environmental burden.

[0024] The beneficial effects of this application are: (1) This application achieves a synergistic balance between rigidity and flexibility by constructing a three-dimensional network comprising flexible alkyl segments, rigid aromatic segments, and modified cyclodextrin crosslinking structures. The flexible segments endow the network with high swelling capacity to accommodate a large number of oil molecules, while the rigid segments provide skeletal support to prevent swelling collapse. The modified cyclodextrin serves as a crosslinking point to maintain the integrity of the network and enhances adsorption selectivity and affinity through host-guest inclusion interaction, thus possessing both high oil absorption capacity and high oil retention rate.

[0025] (2) This application utilizes the phase separation behavior of nonpolar liquid alkane porogens during suspension polymerization to construct in situ a multi-level interconnected pore structure containing mesopores and micropores. This structure not only provides abundant specific surface area but also forms efficient mass transfer channels, significantly shortening the time for oil molecules to penetrate into the cross-linked network and significantly improving adsorption kinetics performance.

[0026] (3) The microspheres prepared in this application have excellent chemical stability and environmental tolerance. The synergistic effect of the rigid aromatic segments and the hydrophobic tert-butyl groups effectively blocks the corrosion of acid and alkaline media, enabling them to maintain stable adsorption performance in strong acid, strong alkali and wide temperature range environments, and are suitable for complex industrial wastewater treatment and marine oil spill emergency response scenarios.

[0027] (4) The preparation process of this application is simple, the raw materials are renewable, and the materials can be efficiently regenerated and recycled through ethanol extraction. After multiple cycles, the performance decay is minimal, which is in line with the principles of green chemistry and has significant prospects for industrial application and economic benefits.

[0028] It should be noted that the technical effects of the second implementation method can be found in the technical effects of the corresponding implementation method in the first aspect, and will not be repeated here.

[0029] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and do not limit this application. Attached Figure Description

[0030] Figure 1 This is a schematic diagram illustrating the synthesis route and structural characterization of β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application. Figure 2 These are photographs of the β-cyclodextrin cross-linked porous oil-absorbing microspheres before and after adsorbing different oils, as described in this application. Figure 3 This is a graph showing the oil absorption performance test results of β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application; Figure 4 This is a test diagram of the recycling performance and environmental stability of β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application; Figure 5 This is a fitting curve of the adsorption kinetics of the β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application; Figure 6 This is a comparison diagram showing the effects of different porogens on the pore structure and oil absorption performance of microspheres in embodiments of this application; Figure 7 Scanning electron microscope (SEM) images of microspheres prepared with different porogens according to embodiments of this application; Figure 8 This is a schematic diagram of the preparation method of β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application; Figure 9 This is a schematic flowchart illustrating the regeneration process of β-cyclodextrin crosslinked porous oil-absorbing microspheres according to an embodiment of this application. Detailed Implementation

[0031] The embodiments of this application will be described below with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of this application from the content disclosed in this specification. This application can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of this application. It should be understood that the preferred embodiments are only for illustrating this application and are not intended to limit the scope of protection of this application.

[0032] In the embodiments of this application, the terms "exemplary" or "for example" are used to indicate that something is an example, illustration, or description. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of this application should not be construed as being more preferred or advantageous than other embodiments or design. Specifically, the use of the terms "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.

[0033] It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of this application. Therefore, the drawings only show the components related to this application and are not drawn according to the number, shape and size of the components in actual implementation. In actual implementation, the form, quantity and proportion of each component can be arbitrarily changed, and the layout of the components may also be more complex.

[0034] Next, see Figures 1-9This application will describe some embodiments of β-cyclodextrin crosslinked porous oil-absorbing microspheres and their preparation methods.

[0035] Example 1 This embodiment provides a β-cyclodextrin crosslinked porous oil-absorbing microsphere. This β-cyclodextrin crosslinked porous oil-absorbing microsphere has a three-dimensional crosslinked network, which includes flexible alkyl segments, rigid aromatic segments, and a modified cyclodextrin crosslinked structure. Specifically, as... Figure 1 (a) and Figure 1 As shown in (b), this three-dimensional cross-linked network design is based on the principle of rigid-flexible synergy in molecular engineering, where each component plays an irreplaceable and mutually beneficial role at the microscale. The flexible alkyl segments are mainly composed of long-chain alkyl ester units, whose molecular chains have high free volume and mobility. Upon contact with oil, they undergo significant conformational changes and swelling, providing the necessary space for oil molecule penetration and storage. Simultaneously, van der Waals forces enable the initial capture of non-polar oil molecules. The rigid aromatic segments contain rigid groups such as benzene rings, serving as physical support nodes in the network. This effectively limits the excessive extension of the flexible segments, preventing the microspheres from collapsing or rupturing due to excessive swelling pressure after oil saturation, thus maintaining the macroscopic morphological integrity and mechanical strength of the material. The modified cyclodextrin crosslinking structure plays a dual role in this network: on the one hand, its polymerizable double bonds act as a chemical crosslinking agent, covalently integrating into the polymer backbone and ensuring the stability of the three-dimensional network; on the other hand, the unique cage-like structure of cyclodextrin—hydrophilic on the outer wall and hydrophobic on the inner cavity—is retained in the network. These hydrophobic cavities can specifically recognize and lock in size-matched organic molecules through host-guest inclusion interactions, significantly enhancing the material's adsorption selectivity and affinity for target pollutants. It should be understood that the above three structural units are not simply a physical superposition, but rather form an organic whole through chemical bonding. The high swelling degree conferred by the flexible segments, the structural support provided by the rigid segments, and the specific adsorption sites contributed by the cyclodextrin work synergistically to fundamentally solve the technical challenge of balancing adsorption capacity and mechanical stability in traditional oil-absorbing materials.

[0036] The β-cyclodextrin cross-linked porous oil-absorbing microspheres have a multi-level interconnected pore structure inside. Specifically, as... Figure 7As shown in (b), this hierarchical interconnected pore structure refers to a three-dimensional mass transfer network formed in situ inside the microspheres, consisting of interconnected macropores, mesopores, and micropores. Unlike conventional porous materials that only have a high specific surface area but isolated or poorly connected pores, the hierarchical interconnected pore structure in this embodiment acts as a highway for oil molecules to diffuse into the interior of the microspheres. Specifically, the micron-sized macropores serve as primary transport channels, allowing the oil phase to rapidly penetrate into the deep layers of the microspheres; the nano-sized mesopores and micropores serve as secondary oil storage spaces and adsorption interfaces, providing abundant specific surface area to accommodate a large number of oil molecules. This hierarchical pore design significantly shortens the diffusion path of oil molecules and reduces mass transfer resistance, enabling the material to maintain a high saturated oil absorption capacity while possessing excellent adsorption kinetics performance, reaching adsorption equilibrium in a short time. Furthermore, the interconnected pore structure also facilitates the entry and exit of solvent during subsequent regeneration, improving the material's recycling efficiency. In summary, this embodiment achieves a comprehensive improvement in the adsorption capacity, adsorption rate, oil retention capacity, and structural stability of oil-absorbing resin microspheres by constructing a rigid-flexible three-dimensional cross-linked network and a multi-level through-pore structure.

[0037] Example 2 In some embodiments, the flexible alkyl segments are copolymerized from long-chain alkyl ester monomers of acrylic acid or methacrylate and short-chain alkyl ester monomers of acrylic acid or methacrylate, while the rigid aromatic segments are copolymerized from tert-butylstyrene monomers. The modified cyclodextrin crosslinking structure is provided by an alkenyl-modified cyclodextrin crosslinking agent. Specifically, this particular monomer combination design aims to precisely control the rigidity-flexibility balance and functional properties of the polymer network at the molecular level. The long-chain alkyl ester monomers of acrylic acid or methacrylate serve as the main hydrophobic swelling units, and their long side chains endow the polymer segments with excellent mobility and free volume, forming the material basis for the material's high oil absorption capacity. The short-chain alkyl ester monomers of acrylic acid or methacrylate serve as auxiliary regulating units, used to optimize the segment packing density and glass transition temperature, preventing the crystallization tendency or insufficient mechanical strength that may result from pure long-chain monomers. The benzene ring structure in the tert-butylstyrene monomers provides the necessary rigid support nodes for the three-dimensional network, effectively resisting the skeletal collapse caused by swelling pressure. Furthermore, its unique tert-butyl groups not only enhance the hydrophobicity of the material but also hinder the erosion of the polymer backbone by polar media through steric hindrance. Alkenyl-modified cyclodextrin crosslinking agents firmly anchor cyclodextrin units in the network through chemical bonding, acting as crosslinking points to maintain network integrity while retaining the host-guest inclusion capacity of the cyclodextrin cavity, thus achieving a synergistic effect of physical adsorption and specific recognition.

[0038] In a preferred embodiment, the long-chain alkyl ester monomer of acrylic acid or methacrylate is dodecyl acrylate, the short-chain alkyl ester monomer of acrylic acid or methacrylate is butyl acrylate, and the tert-butylstyrene monomer is 4-tert-butylstyrene; based on the total mass of the polymeric monomers excluding the crosslinking agent, dodecyl acrylate accounts for 40% to 60%; the remaining polymeric monomers after removing dodecyl acrylate are butyl acrylate and 4-tert-butylstyrene, and the molar percentage of 4-tert-butylstyrene in the mixture of butyl acrylate and 4-tert-butylstyrene is 5% to 55%; the amount of acryloyl-modified β-cyclodextrin is 5% to 15% of the total mass of the polymeric monomers excluding the crosslinking agent. In this embodiment, β-cyclodextrin crosslinked porous oil-absorbing microspheres are prepared by suspension polymerization using dodecyl acrylate (DDA), butyl acrylate (BA), 4-tert-butylstyrene (PTBS) and acryloyl-modified β-cyclodextrin (β-CD-A) as raw materials. To verify the rationality of the above-mentioned proportion range and demonstrate the best technical effect, this embodiment specifically sets an optimal proportion group in which dodecyl acrylate accounts for 50% of the total amount of monomers and 4-tert-butylstyrene accounts for 35% of the remaining monomers for detailed characterization. It should also be understood that the technical objectives of this application can be achieved when the content of dodecyl acrylate is between 40% and 60% and the proportion of 4-tert-butylstyrene in the remaining part is between 5% and 55%.

[0039] The limitation on the above-mentioned ratio range is not a simple numerical selection, but rather the result of in-depth optimization based on the rigid-flexible synergy mechanism. For example... Figure 3 As shown in (a), when the molar fraction of 4-tert-butylstyrene in the remaining monomer portion varies within the range of 5% to 55%, the oil absorption performance of the microspheres exhibits a non-linear trend of first increasing and then decreasing, reaching a peak at around 35%. This phenomenon reveals the microscopic mechanism of rigid-flexible balance: when the 4-tert-butylstyrene content is below 5%, there are too few rigid support points in the polymer network, leading to excessive swelling and even macroscopic structural collapse during oil absorption. Although the initial swelling degree is large, the oil retention rate decreases significantly, and the mechanical strength cannot meet the requirements of practical applications. Conversely, when the 4-tert-butylstyrene content exceeds 55%, the excessively high density of rigid segments severely restricts the mobility of polymer segments, making it difficult for the network to fully expand to accommodate oil molecules, resulting in a significant decrease in the saturated oil absorption ratio. Only within this specific window of 5% to 55%, especially around 35%, does the supporting effect of the rigid skeleton and the swelling capacity of the flexible segments achieve optimal matching, thus realizing the dual optimization of oil absorption capacity and structural stability.

[0040] Furthermore, controlling the amount of acryloyl-modified β-cyclodextrin to 5%–15% of the total monomer mass is also crucial. If the amount is below 5%, the crosslinking density is insufficient and the number of hydrophobic cavities is sparse, making it difficult to form a stable three-dimensional network and provide sufficient specific adsorption sites. If the amount is above 15%, the crosslinking points become too dense, the network pore size shrinks, and this hinders the diffusion and storage of oil molecules. Under the optimal ratio in this embodiment, the prepared β-cyclodextrin crosslinked porous oil-absorbing microspheres were characterized by Fourier transform infrared spectroscopy (FTIR), as shown... Figure 1 As shown in (c), the assignments of the characteristic peaks in the spectrum are as follows: 3380 cm⁻¹ -1 The absorption peak at 2925 cm⁻¹ corresponds to the -OH stretching vibration of β-cyclodextrin. -1 The absorption peak at 1735 cm⁻¹ is due to the stretching vibration of alkyl CH groups. -1 The peak at 1637 cm⁻¹ is the characteristic absorption peak of acrylate C=O. -1 The characteristic peak of the carbon-carbon double bond was significantly weakened compared to the monomer, confirming the occurrence of the copolymerization reaction. The above infrared spectral data strongly demonstrate that β-CD-A has been successfully covalently integrated into the polymer network, and the components have formed the expected three-dimensional cross-linked network structure through chemical bonding, rather than a simple physical blend. This defined chemical structure is the fundamental guarantee for achieving the aforementioned excellent oil absorption performance and stability.

[0041] It should be noted that wavenumber values ​​in FTIR peak assignment have normal testing and representation tolerances. This is because infrared spectrometers themselves have inherent instrument resolution and measurement errors (typically ±2 to ±5 cm). -1 The absorption peak wavenumbers measured by different instruments, under different testing conditions, and even from different batches of samples often vary by several wavenumbers (cm). -1 On the one hand, there may be slight shifts in the peak positions described in the text; on the other hand, the application may also cause a 1-5 cm difference between the peak positions described in the text and those marked in the figures due to the manual rounding of the spectral readings (retaining the units or tens place). -1 The slight discrepancy between the peak positions described in the text and the values ​​labeled in the figures is normal and does not affect the judgment of the attribution of characteristic groups, nor does it affect the core conclusion that "β-cyclodextrin (β-CD-A) has been successfully integrated into the three-dimensional cross-linked network of polymers through covalent bonds".

[0042] The determination of the above peak positions is based on the overall characteristics of the infrared spectrum, mainly according to the chemical groups corresponding to each characteristic absorption peak (such as 3380 cm⁻¹). -1 The vicinity is near the -OH stretching vibration, 2925 cm. -1 The vicinity is characterized by alkyl CH stretching vibrations, 1720–1735 cm⁻¹. -1 The range is the C=O stretching vibration of acrylate, 1636–1637 cm⁻¹ -1The interval is for the C=C stretching vibration of the carbon-carbon double bond. Within ±5cm -1 Within the tolerance range, the above group attribution is completely valid.

[0043] Example 3 In some embodiments, the hierarchical interconnected pore structure comprises mesopores and micropores, with an average pore size of 3.0–6.0 nm. This structure is formed after the nonpolar liquid alkane porogen undergoes phase separation and is removed during polymerization. Specifically, the formation of this hierarchical interconnected pore structure does not rely on physical pore-forming during post-treatment, but rather originates from the thermodynamic phase separation behavior within the suspension polymerization system. In the initial stage of the reaction, the nonpolar liquid alkane porogen is miscible with the mixed monomers to form homogeneous oil droplets. As the polymerization proceeds, polymer segments gradually grow and precipitate from the monomer-porogen mixed solvent. Due to the poor compatibility between the nonpolar liquid alkane and the generated polymer network, the porogen is repelled and enriched into independent liquid-phase microregions. After the polymerization reaction ends and the three-dimensional cross-linked network solidifies, the residual porogen is removed by solvent extraction, and the space originally occupied by the porogen is transformed in situ into interconnected pores. The key to selecting nonpolar liquid alkanes as porogens lies in their moderate difference in solubility parameters with the polymer network. This ensures uniform dispersion in the initial stage of the reaction while allowing for appropriate phase separation in the middle stage of polymerization. This avoids the problems of pore collapse that may occur with polar porogens or the loss of pore structure due to the use of good solvents. This average pore size range (3.0–6.0 nm) covers the typical mesoporous scale, which is beneficial for the rapid penetration of oil molecules through capillary forces and provides sufficient specific surface area to enhance interfacial adsorption, a structural prerequisite for achieving high oil absorption kinetics.

[0044] In a preferred embodiment, the nonpolar liquid alkane porogen is n-dodecane; the BET specific surface area of ​​the hierarchical interconnected pore structure is 3.726–6.0 m². 2 / g, total pore volume is 0.002~0.010cm³ 3 / g, with an average pore size of 3.0–4.5 nm. In this embodiment, n-dodecane was specifically chosen as a pore-forming agent to construct the above-mentioned pore structure. Figure 6 (a) Figure 6 (b) and Figure 7As shown in the comparative experimental results, the pore structure and oil absorption performance of the microspheres obtained by using no porogen, toluene, ethyl acetate, and n-dodecane as porogens, respectively, showed significant differences. When using polar or aromatic solvents such as toluene or ethyl acetate, the phase separation process was delayed or insufficient due to their strong interaction with the polymer segments. This resulted in mostly closed, isolated pores or poorly connected slit pores. Scanning electron microscopy images showed dense surfaces, incomplete internal pore development, correspondingly low BET specific surface areas, and slow oil absorption rates. In contrast, n-dodecane, as a long-chain saturated alkane, possesses a non-polar characteristic that provides just the right amount of thermodynamic incompatibility with copolymer networks containing rigid aromatic segments and flexible alkyl segments. It can undergo spinoline decomposition or nucleation-growth phase separation when the polymerization conversion reaches a critical point, thus forming a multi-level network of macropores, mesopores, and micropores throughout the microsphere. Nitrogen adsorption-desorption tests verified that the BET specific surface area of ​​the microspheres prepared using n-dodecane was consistently between 3.726 and 6.0 μm. 2 Within the / g range (e.g., up to 3.726m under optimal conditions). 2 / g), with a total pore volume of 0.002~0.010cm³. 3 / g (e.g., 0.010cm) 3 / g), with average pore size concentrated in the range of 3.0–4.5 nm (e.g., 3.058 nm).

[0045] The multi-level pore structure parameters obtained from the BET nitrogen adsorption-desorption test are summarized in the table below: This specific pore structure parameter window is the material basis for the excellent oil absorption performance achieved in this application: if the BET specific surface area is less than 3.0 m²... 2 If the surface area is less than 6.0 nm or the average pore size is less than 3.0 nm, the effective mass transfer channels are insufficient, the diffusion resistance of oil molecules increases, and the adsorption equilibrium time is prolonged; if the BET specific surface area is greater than 6.0 nm... 2 A pore size of / g or an average pore diameter greater than 4.5nm often indicates excessively thin pore walls or a high proportion of large pores. While the initial oil absorption rate is fast, the mechanical strength of the framework decreases, making it difficult to maintain a high oil retention rate. Therefore, the specific hierarchical interconnected pore structure induced by n-dodecane maximizes the mass transfer efficiency and storage space of oil molecules while ensuring sufficient mechanical strength of the microspheres. This structure is a necessary structural support for the rigid-flexible synergistic network to achieve optimal oil absorption performance. It should be understood that although this embodiment focuses on the effect of n-dodecane, other nonpolar liquid alkanes with similar carbon numbers (such as n-decane, n-tetradecane, etc.) or mixtures thereof can also be used as alternatives, provided that they can induce the formation of similar hierarchical interconnected pore structures in the polymerization system.

[0046] Example 4 In some embodiments, the saturated oil absorption ratio of β-cyclodextrin cross-linked porous oil-absorbing microspheres for carbon tetrachloride is ≥120 g / g, and for xylene it is ≥90 g / g; the oil retention rate of β-cyclodextrin cross-linked porous oil-absorbing microspheres for both carbon tetrachloride and xylene is ≥90%. Specifically, the above performance indicators are determined by standardized weighing and centrifugation methods. When testing the saturated oil absorption ratio, β-cyclodextrin cross-linked porous oil-absorbing microspheres dried to constant weight are placed in a 200-mesh polypropylene filter bag (the filter bag is pre-wetted with the oil to be tested and drained to deduct the mass error caused by the filter bag's own oil absorption), completely immersed in the oil to be tested (such as carbon tetrachloride or xylene), and allowed to stand at 25±1℃ until equilibrium is reached (usually the mass change is less than 1% after two consecutive weighings), then removed, excess oil is drained from the surface, and the weight is calculated. The saturated oil absorption ratio Q is calculated using the following formula: Q = (m_sat − m0) / m0, where m0 is the initial mass of the dried microspheres and m_sat is the mass after saturated adsorption. The oil samples to be tested were pre-treated with anhydrous sodium sulfate for dehydration and impurity removal. Under the optimal formulation conditions of this embodiment, the saturated oil absorption ratios of the prepared porous oil-absorbing resin microspheres for seven typical oil samples are shown in the table below: The above data demonstrates the broad-spectrum adsorption capacity of this material for oils of different polarities and molecular sizes, significantly superior to similar β-CD-based oil-absorbing materials reported in the literature (79.1–102 g / g). Regarding oil retention rate, centrifugation was used for testing. Porous oil-absorbing resin microspheres that had reached oil saturation were placed in centrifuge tubes along with pretreated polypropylene filter bags. A horizontal rotor (rotor radius 13.5 cm) was used, and centrifuged at 1000 rpm (corresponding to a centrifugal acceleration of approximately 150 g) at room temperature (25 ± 1 °C) for 5 min. The oil retention rate was calculated by comparing the mass change before and after centrifugation. The oil retention rate S was calculated using the following formula: S = (m_cen − m0) / (m_sat − m0) × 100%, where m_cen is the mass after centrifugation. Figure 3As shown in (b), the test results indicate that the porous oil-absorbing resin microspheres achieved an oil retention rate exceeding 85% for all tested oils, with a retention rate of approximately 95% for carbon tetrachloride, xylene, and gasoline, while maintaining a relatively high retention rate of approximately 90% for diesel. This excellent combined oil absorption and retention performance essentially stems from the unique microstructure constructed in Examples 1 to 3: on the one hand, the flexible alkyl segments and multi-level interconnected pore structure provide ample oil storage space and rapid mass transfer channels, ensuring high adsorption capacity; on the other hand, the physical cross-linking nodes formed by the rigid aromatic segments effectively resist the skeletal collapse caused by swelling pressure. Combined with the host-guest inclusion effect of the modified cyclodextrin cavity and the strong van der Waals forces between hydrophobic segments, the oil molecules are firmly locked inside the network, making them difficult to desorb even under centrifugal force, thus achieving a high oil retention rate. This is crucial for preventing secondary leakage in actual oil spill recovery processes.

[0047] As an optional implementation method, the weight loss of β-cyclodextrin cross-linked porous oil-absorbing microspheres after immersion in 18% HCl solution and 48% NaOH solution at 50℃ for 48h was <6%. This characteristic characterizes the structural integrity and durability of the material under extreme chemical environments. The specific test method was as follows: multiple dried microsphere samples were accurately weighed and placed in polytetrafluoroethylene sealed reaction bottles, with a solid-liquid ratio controlled at 1g:100mL. Deionized water, 18% hydrochloric acid solution, and 48% sodium hydroxide solution were added respectively. After sealing, the samples were placed in a 50℃ constant temperature water bath for 48h. After immersion, the samples were removed: acid-immersed samples were repeatedly rinsed with deionized water until neutral; alkali-immersed samples were first neutralized with dilute hydrochloric acid, then thoroughly washed with deionized water until the filtrate pH≈7. The washed samples were placed in a forced-air drying oven, with a heating rate of 2℃ / min, and dried at 60℃ until constant weight. The mass of the dried samples was weighed and the weight loss rate was calculated. Experimental data show that under these stringent conditions, the weight loss rate of the microspheres was 1.78% in deionized water, 2.64% in 18% HCl solution, and 5.83% in 48% NaOH solution, all consistently controlled within 6%. Figure 4As shown in (b), this superior acid and alkali resistance is not possessed by ordinary acrylate polymers, but rather benefits from the specific molecular design of this application. First, the benzene ring in the rigid aromatic segment exhibits high conjugation stability, and the adjacent tert-butyl group generates a significant steric hindrance effect and strong hydrophobic shielding, effectively preventing the penetration of acid and alkali media into the polymer network and the hydrolytic attack on the ester bonds. Second, acryloyl-modified β-cyclodextrin, as a multifunctional crosslinking agent, forms a dense three-dimensional network structure, further restricting the movement and dissolution of polymer segments in corrosive media. Finally, although the multi-level through-pore structure constructed by the nonpolar liquid alkane porogen increases the specific surface area, the pore walls, composed of highly crosslinked hydrophobic polymers, avoid the capillary corrosion problem common in hydrophilic pores. Therefore, even when exposed to high temperature, strong acid and strong alkali environments for a long time, the porous oil-absorbing resin microspheres can still maintain the skeleton without collapsing and the functional groups without being lost, making them capable of meeting the application requirements of complex and harsh scenarios such as deep treatment of chemical wastewater and remediation of acidic mine water, thus solving the industry pain point of poor environmental tolerance of traditional oil-absorbing materials.

[0048] Example 5 like Figure 8 As shown, this embodiment provides a method for preparing β-cyclodextrin crosslinked porous oil-absorbing microspheres. This method is based on suspension polymerization and in-situ phase separation pore-forming technology, constructing a three-dimensional crosslinked network with a multi-level interconnected pore structure in one step. Before starting the preparation, a modified cyclodextrin crosslinking agent (such as acryloyl-modified β-cyclodextrin) needs to be synthesized in advance. The specific synthesis steps are as follows: 6.02 g of potassium hydroxide is dissolved in 250 mL of deionized water, and 20 g of β-cyclodextrin is added under vigorous stirring at room temperature until completely dissolved; the solution is cooled to 0–5 °C, and 14.3 mL of acryloyl chloride is slowly added dropwise through a constant pressure dropping funnel over 30 min (dropping rate 0.2–0.3 mL / min, stirring speed 350 r / min); after the addition is complete, the temperature is raised to 40 °C and the mixture is continued to be heated. The reaction was continued with stirring for 6 hours. After the reaction was completed, the white potassium acrylate byproduct precipitate was removed by vacuum filtration, and the filtrate was collected. The filtrate was evaporated under reduced pressure to remove 75%–80% of the initial aqueous solvent. The remaining concentrate was added to acetone at a volume ratio of concentrate to acetone of 1:8, precipitating a white crude product. The crude product was recrystallized three times using a mixed solvent of deionized water and acetone at a volume ratio of 1:4 (heated to 50°C for complete dissolution, then allowed to cool naturally to 25°C and allowed to stand for 8 hours to crystallize). The crystals were then vacuum filtered and dried to obtain a white powdery β-CD-A with a yield of approximately 70%. The NMR characterization data of the obtained β-CD-A are shown in the table below. The above nuclear magnetic resonance data confirm that the acryloyl group has been successfully grafted onto the β-cyclodextrin molecule.

[0049] Step S100: Prepare an aqueous dispersion containing a dispersant. Specifically, dissolve the dispersant in deionized water to prepare a continuous phase system with a certain viscosity and surface tension. The role of the dispersant is to reduce the interfacial tension between oil and water during subsequent stirring, prevent monomer droplet aggregation, and thus control the particle size distribution and sphericity of the microspheres. For example, polyvinyl alcohol (PVA) can be used as a dispersant, as the hydroxyl groups on its molecular chain can form a stable hydration layer in the aqueous phase, providing steric stabilization for the oil phase droplets. It should be understood that the type and concentration of the dispersant can be adjusted according to the target microsphere particle size, as long as it can maintain stable droplet dispersion in the polymerization system.

[0050] In step S200, an oil-phase mixture comprising a flexible alkyl monomer, a rigid aromatic monomer, a modified cyclodextrin crosslinking agent, an initiator, and a nonpolar porogen is added to an aqueous dispersion to carry out a suspension polymerization reaction, yielding polymer microspheres. Specifically, dodecyl acrylate, butyl acrylate, 4-tert-butylstyrene, acryloyl-modified β-cyclodextrin, an initiator (such as benzoyl peroxide), and a nonpolar liquid alkane porogen (such as n-dodecane) are first mixed uniformly in a predetermined ratio to form a transparent homogeneous oil-phase mixture. This oil phase is then added to the above aqueous dispersion and dispersed into uniformly sized droplets under mechanical stirring, followed by heating to initiate polymerization under inert gas protection. In this process, nonpolar porogens play a crucial role in in-situ pore formation: in the initial stage of the reaction, the porogen is miscible with the monomer, and the system is homogeneous; as the polymerization reaction proceeds, polymer segments gradually grow and precipitate from the monomer-porogen mixed solvent. Due to the thermodynamic incompatibility between the nonpolar porogen and the generated cross-linked polymer network, the porogen is repelled and enriched into independent liquid-phase microdomains; when the polymerization conversion reaches a critical point, these enriched porogen microdomains are fixed by the solidified polymer skeleton, thus forming interconnected pore morphologies in situ inside the microspheres. This phase-separation pore formation mechanism is the core feature that distinguishes this application from traditional post-pore-forming processes. It ensures the integrated molding of the pore structure and the polymer skeleton, avoiding structural damage or pore closure problems that may occur with post-processing pore formation.

[0051] Step S300 involves solvent extraction of the polymer microspheres to remove non-polar porogens, yielding β-cyclodextrin-crosslinked porous oil-absorbing microspheres. Specifically, after the polymerization reaction, the solid microsphere product is collected and repeatedly washed and extracted using a good solvent. For example, acetone and deionized water are used for alternating washing, utilizing the excellent solubility of acetone in non-polar porogens and residual monomers (the principle of "like dissolves like") to completely displace them from the pores inside the microspheres. Simultaneously, water washing removes residual dispersants and water-soluble impurities. This step is not only a purification process but also a crucial step in the final formation of the pore structure: only by completely removing the porogens occupying the pores can the spaces originally filled by the porogens be transformed into effective adsorption cavities and mass transfer channels, thereby endowing the microspheres with the multi-level interconnected pore structure characteristics described in Example 3. If the extraction is incomplete, the residual porogens will block the pores or occupy adsorption sites, severely impairing the oil absorption performance of the material. Through the combination of steps S100 to S300 described above, this application achieves precise control from molecular design to macroscopic morphology, and prepares high-performance oil-absorbing resin microspheres that combine a rigid-flexible synergistic network with a multi-level through-pore structure.

[0052] Example 6 In some embodiments, the dispersant is polyvinyl alcohol, and the initiator is benzoyl peroxide; the suspension polymerization reaction temperature is 70–90°C, and the reaction time is 10–15 h; solvent extraction is performed by alternating washing with acetone and deionized water. Specifically, this embodiment is a further refinement and optimization of the aforementioned basic preparation method. In a specific preparation example, 2.0 g of PVA1799 was dissolved in 100 mL of deionized water and placed in a 250 mL three-necked flask (equipped with a mechanical stirrer at 300 rpm; a reflux condenser; and a nitrogen inlet tube) to prepare a PVA aqueous dispersion with a mass fraction of approximately 2 wt%. Under nitrogen protection, the components were added sequentially according to the following proportions: DDA accounted for 50% of the total monomer, the remaining 50% consisted of BA and PTBS (PTBS accounted for 35 mol% of the BA+PTBS portion), β-CD-A accounted for 7% of the total monomer mass, BPO accounted for 0.7% of the total monomer mass, and dodecane porogen accounted for 10% of the total monomer mass. After purging with nitrogen for 1 hour to remove oxygen, the reaction system was heated to 80°C and reacted at this temperature for 12 hours. After the reaction, the white microsphere product was collected and washed alternately with acetone and deionized water, then dried under vacuum at 50°C to constant weight to obtain DBP microspheres. Polyvinyl alcohol (PVA) was chosen as the dispersant because its molecular chain contains a large number of hydroxyl groups, which can form a protective layer with a certain viscosity in the aqueous phase. This effectively prevents the aggregation of oil phase droplets during stirring through steric hindrance, thus obtaining microsphere precursors with uniform particle size. In practice, PVA-1799, with a high degree of alcoholysis, is preferred. Its dosage is typically controlled between 0.5% and 2.0% of the total monomer mass, ensuring dispersion stability without hindering mass transfer due to excessive viscosity. Benzoyl peroxide (BPO) was chosen as the initiator because its decomposition activation energy matches the aforementioned temperature window well. At a reaction temperature of 70–90°C, BPO can decompose at a moderate rate to generate free radicals, inducing a stable polymerization reaction and avoiding localized overheating or rapid polymerization caused by excessively rapid exothermic reactions. This is crucial for maintaining the fine porous structure formed by phase separation. If the temperature is below 70°C, the initiation efficiency is insufficient, the reaction cycle is too long, and the conversion rate is low. If the temperature is above 90°C, the reaction rate is difficult to control, easily causing stress concentration or even rupture within the microspheres. Therefore, the reaction time is set to 10–15 hours to ensure that the monomer conversion rate reaches over 95% within the aforementioned temperature range, while providing sufficient thermodynamic equilibrium time for the phase separation process, allowing the porogen microdomains to be completely solidified within the polymer backbone. In a preferred embodiment of this application, the reaction temperature is set to 80°C, and the reaction time is 12 hours, at which the microspheres obtained exhibit the best overall performance.

[0053] Regarding the solvent extraction step, this embodiment specifically emphasizes the use of alternating washing with acetone and deionized water. This is not a simple cleaning operation, but a crucial process step that determines the effectiveness of the final pore structure. Specifically, acetone, as a good organic solvent, can efficiently dissolve and displace residual non-polar porogens (such as n-dodecane) and unreacted hydrophobic monomers inside the microspheres based on the principle of "like dissolves like." Deionized water, on the other hand, utilizes its polarity difference to specifically elute water-soluble dispersants (PVA) and other polar impurities adsorbed on the surface of the microspheres. The reason for using "alternating" washing instead of continuous washing with a single solvent is that the microspheres contain multi-level complex channels from macropores to micropores. A single solvent often cannot effectively remove residues of different polarities, and sudden changes in solvent polarity can easily cause uneven swelling or shrinkage on the surface of the microspheres, leading to pore collapse or blockage. Through multiple alternating treatments with acetone and water, the gradient change in the polarity of the two solvents can be used to drive the residues from the deep layers of the microspheres to the surface and completely remove them, thereby maximizing the unblocking of the pores and exposing fresh adsorption interfaces. Experiments show that after this rigorous alternating washing treatment, the residual amount of pore-forming agent inside the microspheres can be reduced to below 500 ppm, and the residual dispersant is also effectively removed. This not only ensures the chemical purity of the material, but also directly contributes to the high BET specific surface area and excellent oil absorption kinetics as described in Example 3. It should be understood that although this embodiment uses the PVA / BPO system and acetone / water washing as examples for detailed description, other dispersant or initiator systems with similar functions, or mixed solvent washing schemes based on the same solubility parameter principle, should be considered within the scope of protection of this application, provided that they achieve the same technical effect without departing from the concept of this application.

[0054] Example 7 In some embodiments, such as Figure 9As shown, the preparation method also includes a step of regenerating the β-cyclodextrin cross-linked porous oil-absorbing microspheres after oil adsorption: Step S400, the β-cyclodextrin cross-linked porous oil-absorbing microspheres after oil adsorption are immersed in ethanol for washing, and then dried for recycling; after 10 cycles, the oil absorption ratio is maintained at ≥75%. Specifically, the regeneration process is a key indicator for evaluating the practical application value of oil-absorbing materials. In this embodiment, ethanol is used as the regeneration solvent, and its selection is based on a unique solvent selectivity mechanism. Ethanol, as a moderately polar organic solvent, exhibits excellent solubility for most nonpolar and weakly polar oils (such as alkanes, aromatic hydrocarbons, and halogenated hydrocarbons). Driven by concentration gradients and molecular diffusion, it efficiently displaces oil molecules trapped within the multi-level interconnected channels and three-dimensional cross-linked network of microspheres. Simultaneously, because the β-cyclodextrin-crosslinked porous oil-absorbing microsphere framework of this application is composed of highly crosslinked hydrophobic polymers and contains rigid aromatic segments and modified cyclodextrin crosslinking structures, it undergoes only extremely limited swelling in ethanol without dissolving or undergoing irreversible structural deformation. This "oil-soluble but not framework-soluble" characteristic ensures that the microporous structure and surface chemistry of the microspheres are completely preserved during oil desorption, providing almost identical active sites and mass transfer channels for the next adsorption cycle. In contrast, while using strong solvents such as acetone and tetrahydrofuran for regeneration results in more thorough deoiling, it can easily lead to excessive swelling or even partial dissolution of the polymer network, causing pore collapse and a decrease in mechanical strength. Using only water or low-polarity solvents for cleaning, however, fails to remove deeply adsorbed oils, resulting in accumulated residues and a rapid decline in performance. Therefore, ethanol immersion washing represents the optimal process choice that strikes the best balance between regeneration efficiency and structural protection.

[0055] In practice, the regeneration process typically includes the following steps: Saturated β-cyclodextrin-crosslinked porous oil-absorbing microspheres are immersed in anhydrous ethanol at a solid-liquid ratio of 1g:100mL, and washed at room temperature for 30 minutes, with appropriate agitation during this period to enhance mass transfer; subsequently, the microspheres are filtered out, and the above soaking and washing operation is repeated three times with fresh anhydrous ethanol to ensure complete oil removal; finally, the washed microspheres are dried in a 50℃ vacuum oven to constant weight, thus completing one regeneration cycle. Figure 4As shown in (a), after the standardized regeneration process described above, the oil absorption ratio of the β-cyclodextrin crosslinked porous oil-absorbing microspheres remained stable throughout 10 consecutive "adsorption-ethanol desorption-drying" cycles, with a retention rate of over 75% after the 10th cycle (e.g., around 80% under certain preferred conditions). This data strongly demonstrates the material's excellent structural memory and fatigue resistance: even after repeated swelling-shrinkage stress cycles and erosion by solvent molecules, the rigid aromatic chain segment support nodes and modified cyclodextrin crosslinking points within the material remained stable, and the multi-level interconnected pore structure did not experience significant collapse or blockage. This superior cyclic stability not only significantly extends the material's service life and reduces the cost of consumables for a single oil spill treatment but also reduces secondary solid waste pollution from discarded adsorbents, giving it significant industrial application potential and economic benefits in scenarios such as marine oil spill emergency recovery, deep purification of industrial oily wastewater, and resource utilization of organic solvents. It should be understood that although this embodiment uses ethanol as an example for detailed description, other alcohol solvents (such as methanol, isopropanol, etc.) or their mixtures that have good solubility in oil and do not damage the microsphere skeleton can also be used as alternative regeneration media without departing from the concept of this application, as long as they can achieve the same regeneration effect and maintain the integrity of the material structure.

[0056] Furthermore, this application systematically characterized the adsorption kinetics, temperature adaptability, and adsorption thermodynamics of the porous oil-absorbing resin microspheres. The adsorption kinetic fitting results are as follows: Figure 5 (a) Figure 5 As shown in (b).

[0057] In terms of adsorption kinetics, the oil absorption capacity was measured at different times under 25℃ conditions. The oil absorption process of the porous oil-absorbing resin microspheres was fitted and analyzed using a pseudo-first-order kinetic model, a pseudo-second-order kinetic model, and an intraparticle diffusion model. The coefficient of determination R0 of the pseudo-first-order model was... 2 The values ​​were 0.99986 (CCl4), 0.99974 (CHCl3), 0.99995 (xylene), and 0.99946 (toluene), respectively. The goodness of fit was significantly higher than that of the pseudo-second-order kinetic model, proving that the oil absorption process is dominated by physical adsorption. The kinetic fitting parameters, such as the rate constants and coefficients of determination, for each model are shown in Table 1. Table 1 shows the fitting parameters for the pseudo-first-order kinetic, pseudo-second-order kinetic, and intraparticle diffusion models under four oily solvents, where K1 is the pseudo-first-order rate constant, K2 is the pseudo-second-order rate constant, Kᵢ is the intraparticle diffusion rate constant, and R... 2 The coefficients of determination are used for fitting; as shown in Table 1, the pseudo-first-order kinetics R0 of the four oil product systems are... 2 All values ​​are greater than 0.999, further confirming that the oil absorption process conforms to the pseudo-first-order kinetic adsorption characteristics; the intraparticle diffusion parameters show that the adsorption process is divided into three mass transfer processes.

[0058] Table 1. Fitting kinetic parameters of three absorption models for four oily solvents. The equilibrium adsorption capacities of microspheres prepared under different porogen conditions for various hazardous oily chemicals are shown in Table 2. (Table 2 corresponds to...) Figure 6 The test data in (a) show that the DBP / Dodecane group, which uses n-dodecane as a porogen, has the highest overall equilibrium adsorption capacity for various oil products; the DBP group without a porogen has the lowest adsorption capacity. This result is consistent with the aforementioned pore structure analysis conclusions.

[0059] Table 2. Equilibrium adsorption capacity (g·g⁻¹) of DBP microspheres prepared with different pore-forming agents for hazardous oily chemicals. As shown above, the intraparticle diffusion fitting curve exhibits a three-stage mass transfer characteristic: the first stage is the rapid wetting and diffusion of oil molecules on the outer surface of the microspheres; the second stage is the slow diffusion process of oil within the porous channels, which is the rate-controlling step of the entire adsorption process; and the third stage is when the internal adsorption tends to reach equilibrium. The flexible hydrophobic alkyl chain achieves rapid capture of oil molecules through van der Waals forces, determining the adsorption kinetic rate; the rigid β-cyclodextrin hydrophobic cavity provides stable adsorption sites through host-guest inclusion interaction, enhancing the saturated adsorption capacity.

[0060] In terms of temperature adaptability, such as Figure 4 As shown in (b), the saturated oil absorption capacity of the porous oil-absorbing resin microspheres was measured within a temperature range of −20℃ to 60℃. The results show that the porous oil-absorbing resin microspheres maintain a stable oil absorption capacity of 83–89 g / g throughout the entire temperature range, exhibiting excellent temperature adaptability. The results for acid and alkali immersion weight loss are shown in [reference needed]. Figure 4 (b) Inner illustration. At low temperatures, the adsorption amount is slightly lower due to increased oil phase viscosity and restricted chain segment movement. At high temperatures, the adsorption amount decreases slightly due to weakened van der Waals forces, but the overall change is very small.

[0061] In terms of adsorption thermodynamics, adsorption thermodynamic parameters (ΔG, ΔH, ΔS) were calculated by combining adsorption data at multiple temperatures. The thermodynamic results confirmed that the adsorption process can proceed spontaneously, and the adsorption enthalpy characteristics further corroborated that the adsorption is essentially physical adsorption. The driving force of adsorption comes from the capillary force of the porous framework, the van der Waals effect of the hydrophobic segments, and the host-guest inclusion synergistic effect of the β-cyclodextrin lumen.

[0062] Comparative Example 1 To verify the critical significance of the 5%–55% molar ratio of 4-tert-butylstyrene in the remaining monomer fraction, this comparative example, following the preparation method of Example 6, adjusted the content of 4-tert-butylstyrene (PTBS) to outside this range. Specifically, in Comparative Example 1-1, the molar fraction of PTBS in the remaining monomer fraction was set to 0% (i.e., the flexible network consisted only of dodecyl acrylate and butyl acrylate), and in Comparative Example 1-2, the PTBS content was set to 70%. The test results showed that when the PTBS content was 0%, due to the complete absence of the physical support nodes of rigid aromatic segments in the polymer network, the microspheres underwent excessive swelling upon contact with oil, macroscopically exhibiting a gel-like soft substance rather than independent particles. Although the initial oil absorption rate was relatively fast, severe collapse occurred because the skeleton could not withstand the swelling pressure, resulting in an oil retention rate of less than 60% for carbon tetrachloride. Furthermore, the microspheres were easily damaged and lost during centrifugation or extrusion recovery, losing the mechanical stability required for practical applications. Conversely, when the PTBS content reaches 70%, the excessively high rigid segment density significantly reduces the free volume of the three-dimensional cross-linked network, severely freezing the segment mobility and making it difficult for oil molecules to penetrate into the network. This results in a saturated oil absorption rate of only about 45 g / g for carbon tetrachloride, far lower than the 122.6 g / g in Example 4. Figure 3 As shown in (a), the oil absorption performance exhibits a significant nonlinear peak characteristic with the change of PTBS content. Only within the range of 5% to 55% specified in this application, especially around 35%, can the optimal balance between rigidity and flexibility be achieved. This comparative result strongly demonstrates that simply increasing either the flexible monomer or the rigid monomer cannot obtain an oil-absorbing material with excellent comprehensive performance. The formulation range in this application is based on a specific selection of the rigidity-flexibility synergistic mechanism, rather than simple numerical optimization.

[0063] Comparative Example 2 To verify the irreplaceable role of nonpolar liquid alkane porogens in constructing hierarchical interconnected pore structures, this comparative example, following the preparation method of Example 6, included a blank group (Comparative Example 2-1) without porogens and a control group (Comparative Example 2-2) using the polar solvent toluene as a porogen. In Comparative Example 2-2, the mass of toluene added was the same as the mass of n-dodecane porogen added in Example 6. Specifically, due to the lack of a porogen-induced phase separation process, the polymerization product in Comparative Example 2-1 was a dense, solid microsphere, and nitrogen adsorption-desorption testing showed its BET specific surface area was only 0.8 m². 2The surface area is almost entirely devoid of effective pores, meaning oil molecules can only be adsorbed through surface wetting. The saturated oil absorption rate for carbon tetrachloride is less than 20 g / g, and reaching adsorption equilibrium takes more than 24 hours. Although Comparative Example 2-2 added the same amount of toluene as Example 6, toluene, being a good solvent for polymer segments, exhibits excellent compatibility with the resulting copolymer during polymerization, making effective thermodynamic phase separation difficult. This results in the formation of mostly closed, isolated pores or poorly connected slit-like pores after removal. Figure 7 As shown in the scanning electron microscope image (c), the surface of the toluene-porous microspheres is relatively smooth, and the interior lacks the abundant macroporous-mesoporous interconnected network found in Example 2; the corresponding BET specific surface area is only 2.1 m². 2 / g, far below the 5.0–6.0m required in this application. 2 / g range. Reflecting on performance, its adsorption kinetics for xylene are significantly slower than in Example 2, and the saturated oil absorption ratio decreases by approximately 30%. For example... Figure 6 As shown, different porogens have vastly different effects on oil absorption performance, which fully demonstrates that not all organic solvents can be used as porogens in this application. Only non-polar liquid alkanes (such as n-dodecane) can utilize the difference in solubility parameters between them and specific copolymer networks to construct in situ a multi-level through-pore structure with both high specific surface area and high connectivity. This is a key prerequisite for achieving high oil absorption kinetics.

[0064] Comparative Example 3 To verify the unique contribution of the modified cyclodextrin crosslinking structure to improving adsorption capacity compared to traditional chemical crosslinking agents, this comparative example follows the preparation method of Example 6, using an equal mass of the conventional small molecule crosslinking agent N,N'-methylenebisacrylamide (MBA) to replace acryloyl-modified β-cyclodextrin (β-CD-A) to prepare microspheres. Specifically, although MBA can also form a stable three-dimensional crosslinking network, and the crosslinking density of the microspheres can be adjusted to be comparable to that of Example 2, the saturated oil absorption ratio of the microspheres prepared with MBA for carbon tetrachloride is only 78 g / g, which is about 36% lower than that of Example 2. This significant performance gap reveals the fundamental difference in the adsorption mechanisms of the two crosslinking agents: MBA only provides purely chemical crosslinking points, and the oil absorption of the material relies entirely on the van der Waals forces of the flexible alkyl segments and the capillary coagulation of the channels; while β-CD-A, in addition to serving as a crosslinking point to maintain network integrity, can also specifically capture size-matched organic molecules through host-guest inclusion interactions by retaining cyclodextrin hydrophobic cavities in its molecule. This dual mechanism of "physical adsorption + supramolecular recognition" significantly increases the upper limit of oil storage per unit mass of material. Furthermore, due to the lack of anchoring effect from cyclodextrin cavities, the oil absorption retention rate of the microspheres prepared in Comparative Example 3 decreased to below 60% after the 5th cycle in the ethanol regeneration cycle test, indicating that adsorption relying solely on van der Waals forces is more prone to irreversible loss during repeated swelling-shrinkage processes. Therefore, the introduction of alkenyl-modified cyclodextrin crosslinking agents is not a simple component replacement, but a core structural design that endows the material with high adsorption capacity and excellent cycling stability, further demonstrating the inventiveness of the technical solution in this application.

[0065] In summary, through the reverse verification experiments of Examples 1 to 3, it is clear that deviating from the monomer ratio range specified in this application leads to an imbalance between rigidity and flexibility; selecting the wrong type of pore-forming agent leads to defects in the pore structure; and replacing the core modified cyclodextrin crosslinking agent results in the loss of the adsorption mechanism. These comparative results, from the opposite perspective, confirm that there is a close synergistic relationship among the various technical characteristics of the β-cyclodextrin crosslinked porous oil-absorbing microspheres of this application. Their excellent oil absorption performance, oil retention rate, and environmental stability are the inevitable result of the combined effect of specific components and specific structures, rather than something that can be easily obtained by simply superimposing conventional methods or conducting a limited number of experiments in the prior art.

[0066] Application Examples To further verify the technical effectiveness and practical value of the β-cyclodextrin cross-linked porous oil-absorbing microspheres prepared in the aforementioned embodiments of this application in real-world application scenarios, this application embodiment simulates three typical working conditions: marine oil spill emergency response, deep treatment of industrial oily wastewater, and material regeneration and recycling. It should be understood that the following application scenarios are merely illustrative and do not limit the scope of protection of this application. The β-cyclodextrin cross-linked porous oil-absorbing microspheres are also applicable to other similar scenarios such as organic hazardous chemical spill response and laboratory solvent recovery.

[0067] In marine oil spill emergency response scenarios, the β-cyclodextrin cross-linked porous oil-absorbing microspheres prepared in Example 2 of this application were spread onto a simulated oil layer on the surface of seawater. Due to the excellent hydrophobic and oleophilic properties of these microspheres and their lower density than water, they can quickly float on the water surface and selectively adsorb oil without absorbing water. Figure 2 As shown in (a)-(h), after contact with different oils such as carbon tetrachloride, xylene, and gasoline, the microspheres changed from white to the corresponding oil color or a transparent swollen state within minutes, visually demonstrating their rapid response capability. More importantly, in actual salvage or mechanical recovery processes, the saturated microspheres exhibited extremely high oil retention performance. Based on the test data from Example 4 above, the oil retention rate of the microspheres for carbon tetrachloride and xylene was ≥90%. This means that when subjected to wave impact, compression, or centrifugal force, the adsorbed oil can still be firmly locked inside the three-dimensional cross-linked network and multi-level through-pore structure, effectively avoiding the dripping phenomenon common in traditional oil-absorbing materials, thereby preventing secondary pollution and significantly improving the efficiency and environmental safety of oil spill recovery operations.

[0068] In the deep treatment of industrial oily wastewater, the environmental tolerance and deep purification capabilities of this microsphere were investigated for chemical wastewater with complex composition and large pH fluctuations. Simulation experiments showed that even under conditions where the pH value deviated extremely from neutral, the microsphere maintained structural integrity and functional stability. Specifically, the weight loss rate of the β-cyclodextrin crosslinked porous oil-absorbing microspheres after soaking in 18% HCl solution and 48% NaOH solution at 50℃ for 48 hours was <6%. This is attributed to the chemically inert framework constructed by rigid aromatic segments and tert-butyl groups, which enables it to resist the hydrolytic attack of ester bonds and the erosion of polymer networks by strong acids and bases. Therefore, when treating oily systems such as electroplating wastewater, pickling wastewater, or alkaline degreasing wastewater, this microsphere can be directly added without pre-adjusting the wastewater pH value, which not only simplifies the process but also avoids the problem of adsorbent failure caused by water quality fluctuations. Meanwhile, its internal multi-level through-pore structure exhibits excellent mass transfer and capture capabilities for emulsified oil and soluble organic solvents, enabling deep oil removal and compliant discharge of wastewater.

[0069] In terms of oil recovery and material regeneration, this application example verifies the economic viability of recycling the microspheres. The saturated β-cyclodextrin-crosslinked porous oil-absorbing microspheres were immersed in anhydrous ethanol for washing. Utilizing ethanol's excellent solvent properties for oil and its non-destructive nature on the microsphere framework, efficient oil desorption and recovery were achieved. Testing revealed that the preparation method also includes a step of regenerating the β-cyclodextrin-crosslinked porous oil-absorbing microspheres after oil adsorption: the microspheres were immersed in ethanol for washing, followed by drying, enabling recycling; after 10 cycles, the oil absorption ratio remained ≥75%. This result indicates that even after multiple swelling-shrinkage cycles and solvent rinsing, the rigid-flexible synergistic network and hierarchical pore structure of the microspheres did not undergo irreversible collapse or blockage, exhibiting excellent structural memory and fatigue resistance. This regenerable characteristic not only significantly reduces the cost of consumables for single oil spill treatment but also reduces the pressure of solid waste disposal from discarded adsorbents, meeting the industrial needs of green chemistry and sustainable development, and demonstrating significant economic and environmental benefits.

[0070] The above embodiments are merely preferred embodiments provided to fully illustrate this application, and the scope of protection of this application is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on this application are all within the scope of protection of this application.

Claims

1. A β-cyclodextrin cross-linked porous oil-absorbing microsphere, characterized in that, The β-cyclodextrin crosslinked porous oil-absorbing microspheres have a three-dimensional crosslinked network, which includes flexible alkyl segments, rigid aromatic segments, and modified cyclodextrin crosslinked structures. The β-cyclodextrin cross-linked porous oil-absorbing microspheres have a multi-level through-pore structure inside.

2. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 1, characterized in that, The flexible alkyl segment is formed by copolymerization of long-chain alkyl ester monomers of acrylic acid or methacrylate and short-chain alkyl ester monomers of acrylic acid or methacrylate, the rigid aromatic segment is formed by copolymerization of tert-butylstyrene monomers, and the modified cyclodextrin crosslinking structure is provided by an alkenyl-modified cyclodextrin crosslinking agent.

3. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 2, characterized in that, The long-chain alkyl ester monomer of acrylic acid or methacrylate is dodecyl acrylate, the short-chain alkyl ester monomer of acrylic acid or methacrylate is butyl acrylate, and the tert-butylstyrene monomer is 4-tert-butylstyrene; The dodecyl acrylate comprises 40% to 60% of the total mass of polymeric monomers excluding the crosslinking agent, and the remaining polymeric monomers consist of butyl acrylate and 4-tert-butylstyrene, wherein the 4-tert-butylstyrene comprises 5% to 55% of the total mass of butyl acrylate and 4-tert-butylstyrene; the alkenyl-modified cyclodextrin crosslinking agent is acryloyl-modified β-cyclodextrin, and its amount is 5% to 15% of the total mass of polymeric monomers excluding the crosslinking agent.

4. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 1, characterized in that, The multi-level through-hole structure includes mesopores and micropores, with an average pore size of 3.0–6.0 nm; The multi-level through-pore structure is formed by the phase separation and removal of a non-polar liquid alkane porogen during polymerization.

5. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 4, characterized in that, The nonpolar liquid alkane pore-forming agent is n-dodecane; The BET specific surface area of ​​the multi-level through-hole structure is 3.726–6.0 m². 2 / g, total pore volume is 0.002~0.010cm³ 3 / g, with an average pore size of 3.0–4.5 nm.

6. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 3, characterized in that, The β-cyclodextrin cross-linked porous oil-absorbing microspheres have a saturated oil absorption rate of ≥120g / g for carbon tetrachloride and a saturated oil absorption rate of ≥90g / g for xylene. The β-cyclodextrin cross-linked porous oil-absorbing microspheres have an oil retention rate of ≥90% for both carbon tetrachloride and xylene.

7. The β-cyclodextrin cross-linked porous oil-absorbing microspheres according to claim 6, characterized in that, The weight loss of the β-cyclodextrin cross-linked porous oil-absorbing microspheres after soaking in 18% HCl solution and 48% NaOH solution at 50°C for 48 h was <6%.

8. A method for preparing β-cyclodextrin cross-linked porous oil-absorbing microspheres, used to prepare the β-cyclodextrin cross-linked porous oil-absorbing microspheres according to any one of claims 1-7, characterized in that, Includes the following steps: Prepare an aqueous dispersion containing a dispersant; An oil phase mixture comprising flexible alkyl monomers, rigid aromatic monomers, modified cyclodextrin crosslinking agents, initiators, and nonpolar porogens is added to the aqueous dispersion to carry out a suspension polymerization reaction to obtain polymer microspheres. The polymer microspheres were subjected to solvent extraction to remove the nonpolar porogen, resulting in the β-cyclodextrin crosslinked porous oil-absorbing microspheres.

9. The preparation method according to claim 8, characterized in that, The dispersant is polyvinyl alcohol, and the initiator is benzoyl peroxide; The suspension polymerization reaction is carried out at a temperature of 70–90°C for 10–15 hours. The solvent extraction process involves alternating washing with acetone and deionized water.

10. The preparation method according to claim 8, characterized in that, The preparation method further includes a step of regenerating the β-cyclodextrin cross-linked porous oil-absorbing microspheres after oil adsorption: The β-cyclodextrin cross-linked porous oil-absorbing microspheres, after adsorbing oil, are immersed in ethanol for washing and then dried for recycling; after 10 cycles, the oil absorption ratio is maintained at ≥75%.